ALASAN, FUNGSI DAN PENILAIAN PENGGUNAAN STRAATTAL PADA EPISODE PERTAMA DE TATTA’S (2024) - Presilla, Rusmasiela Mewipiana; Djarwo, Andrea Pradsna Paramita (Multikultura, 2025)
This study examines the use of straattaal vocabulary in the television series De Tatta’s (2024), along with language attitudes and linguistic accommodation among youth in the Randstad region of the Netherlands. Straattaal is a form of street language that has developed within the Netherlands’ multicultural urban environments and is primarily used by young people as a means of social expression and identity. The research employs a descriptive qualitative method, combining dialogue analysis from the first episode of De Tatta’s with data collected through questionnaires distributed to respondents residing in the Netherlands. The analysis is based on Leech’s (1981) theory of language functions, Niceforo’s (in Partridge, 1933) framework on the use of slang, Lambert’s (1967) theory of language attitudes, and Giles’ (1987) communication accommodation theory. The findings indicate that straattaal functions as an expressive, informative, directive, and phatic tool of communication. Most respondents demonstrate a high level of understanding of straattaal vocabulary and tend to adopt a convergent attitude in their interactions. However, the use of straattaal by the character Daan is generally perceived negatively by the respondents.